THE UP SCHOOL OF LIBRARY AND INFORMATION STUDIES: CONTINUING THE TRADITION OF EXCELLENCE IN LIS EDUCATION - Aguirre, Vyva Victoria M. (Journal of Philippine Librarianship, 2012)
Discusses the traditional and new competencies of librarians and how the UP School of Library and Information Studies fulfills its goals and commitment to continue the tradition of excellence in LIS education.
Keywords: School of Library and Information Studies, history, library education